Growing apart or moving together? Synchronization of informal and formal economy cycles - Ceyhun Elgin; M. Ayhan Kose; Franziska Ohnsorge; Shu Yu (Koç University-TÜSIAD Economic Research Forum (ERF), 2021)
We study the degree of synchronization between formal- and informal-economy business cycles. Using a comprehensive database of informal activity that covers a wide range of informality measures from almost 160 countries over the 1990-2018 period, we report two major results. First, fluctuations in informal-sector output are strongly positively correlated with those in formal-sector output. In contrast, fluctuations in informal employment are largely uncorrelated with those in formal-sector output. Second, movements in the formal economy tend to spillover to the informal economy. Using a novel set of instrumental variables, we show that fluctuations in formal-sector output "cause" movements in informal-sector output.
Keywords: E26; E32; J46; O17; 330; Informal economy; self-employment; business cycle